Offering Global Collaboration Services beyond CERN and HEP. Issue 5 (December 2015) - Fernandes, J; Ferreira, P; Baron, T
Abstract: The CERN IT department has built over the years a performant and integrated ecosystem of collaboration tools, from videoconference and webcast services to event management software. These services have been designed and evolved in very close collaboration with the various communities surrounding the laboratory and have been massively adopted by CERN users. To cope with this very heavy usage, global infrastructures have been deployed which take full advantage of CERN's international and global nature. If these services and tools are instrumental in enabling the worldwide collaboration which generates major HEP breakthroughs, they would certainly also benefit other sectors of science in which globalization has already taken place. Some of these services are driven by commercial software (Vidyo or Wowza for example), some others have been developed internally and have already been made available to the world as Open Source Software in line with CERN's spirit and mission. Indico for example is now installed in 100+ institutes worldwide. But providing the software is often not enough and institutes, collaborations and project teams do not always possess the expertise, or human or material resources that are needed to set up and maintain such services. Regional and national institutions have to answer needs, which are growingly global and often contradict their operational capabilities or organizational mandate and so are looking at existing worldwide service offers such as CERN's. We believe that the accumulated experience obtained through the operation of a large scale worldwide collaboration service combined with CERN's global network and its recently- deployed Agile Infrastructure would allow the Organization to set up and operate collaborative services, such as Indico and Vidyo, at a much larger scale and on behalf of worldwide research and education institutions and thus answer these pressing demands while optimizing resources at a global level. Such services would be built over a robust and massively scalable Indico server to which the concept of communities would be added, and which would then serve as a hub for accessing other collaboration services such as Vidyo, on the same simple and successful model currently in place for CERN users. This talk will describe this vision, its benefits and the steps that have already been taken to make it come to life.